Knowledge and perception regarding molar incisor hypomineralisation among dental students and dental hygienist students in Spain: a cross-sectional study - Vallivana Tarazona-Valero; José Manuel Almerich-Silla; José Enrique Iranzo-Cortés; José Carmelo Ortolá-Siscar; Teresa Almerich-Torres (BMC, 2024)
Abstract Background Molar incisor hypomineralisation (MIH) has a high prevalence in the Spanish pediatric population and is a precursor of carious lesions in teeth in which it is present. Although this pathology is included in the curricula of the Degree in Dentistry and the Training Cycle in Oral Hygiene in our country, the contents currently taught seem to be insufficient in relation to the level of knowledge that we have today about this condition. Methods A digital questionnaire of 18 questions was sent to a sample of 448 students attending the 4th and 5th year of the Degree in Dentistry and 2nd year of the Training Cycle in Oral Hygiene from different universities and vocational training centers in the Valencian Community. Descriptive and multivariate statistical analysis of the data was subsequently performed. Results Of the 290 questionnaires that were obtained, 53.8% were from students attending the 2nd year of a training course in oral hygiene and 46.2% were from students pursuing a degree in dentistry. Most of the respondents had heard about MIH (75.2%), mainly through master classes. However, most students had difficulties distinguishing MIH lesions from other lesions (58.3%). The degree of knowledge about MIH was greater among dental students in all the aspects evaluated: prevalence, diagnosis, prevention, and treatment. Of all the students, 83.8% were interested in increasing their training on MIH, especially in the areas of diagnosis and treatment. Conclusion The results of the present study justify the need to expand the content on MIH, both theoretical and practical, in the educational curricula of the Degree in Dentistry and Integrated Vocational Training Centers in Spain.